Pemicuan Community Led Total Sanitation di Jorong Ronah Bengkek Kecamatan Kapur IX Kabupaten 50 Kota - Zulkarnaini Zulkarnaini; Elva Gusmeri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Community Led Total Sanitation (CLTS) is an approach to changing hygiene and sanitation behaviour through community empowerment with a triggering method that aims to change the behaviour of people who defecate anywhere. Environmental-based diseases, primarily related to water-borne diseases, still dominate the prevalence of diseases in Indonesia. Changing hygiene and sanitation behaviour through community empowerment is needed to improve the health status of the community as high as possible. Community service activities were conducted through interviews, triggering activities and community observations. The flow of triggering activities were introductions, conveying intentions and objectives, atmosphere building, identification of local languages, simple mapping, counting faeces, transect walk, water contamination paths, discussions, social contracts, and free defecation commitment. Participants who previously did not have latrine facilities became aware of and committed to constructing latrines independently. The village where this activity has been carried out will soon become an open defecation-free village. Become a promotor for monitoring and triggering activities for people to stop open defecation.